An Analysis of Illocutionary Acts Found in Kim Namjoon Speech (Leader of BTS) at the United Nation - Yovita Miftahsari Suseno; Pariyanto Pariyanto (Sintuwu Maroso Journal of English Teaching, 2022)
Kim Namjoon is the only representative of the Korean idol chosen by UNICEF to deliver a speech at the general assembly. BTS is of considerable concern to today's youth since its songs are evaluated as encouraging and helpful in the face of struggle. Thespeech entitled